Role of School Bullying Involvement in Depression, Anxiety, Suicidality, and Low Self-Esteem Among Adolescents With High-Functioning Autism Spectrum Disorder - Chou, Wen-Jiun; Wang, Peng-Wei; Hsiao, Ray C.; Hu, Huei-Fan; Yen, Cheng-Fang (Frontiers in Psychiatry, 2020)
This study aimed to compare the severities of psychopathologies and the level of self-esteem among 219 adolescents with high-functioning autism spectrum disorder (ASD) who were classified into pure perpetrators, pure victims, perpetrator-victims, and neutrals in Taiwan. The experiences of school bullying involvement in the previous 1 year were measured using the Chinese version of the School Bullying Experience Questionnaire. The severities of depression, anxiety, and suicidality were measured using the Center for Epidemiological Studies Depression Scale, the Multidimensional Anxiety Scale for Children, and the 5-item questionnaire from the epidemiological version of the Kiddie Schedule for Affective Disorders and Schizophrenia, respectively. The level of self-esteem was measured using the Rosenberg Self-Esteem Scale. The results indicated that compared with the self-reported neutrals, the self-reported perpetrator-victims and pure victims had more severe depression and anxiety. No difference in depression, suicidality, anxiety, and self-esteem was found among the four groups of various parent-reported bullying involvement experiences. Mental health problems in adolescents with ASD who experienced bullying victimization should be routinely surveyed.